2008
DOI: 10.1007/s10620-008-0260-8
|View full text |Cite
|
Sign up to set email alerts
|

Does Cyclophosphamide Play a Protective Role Against Neuronal Loss in Chronic T. cruzi Infection?

Abstract: In this study, we verified the possible role of cyclophosphamide (CY) in protecting or not against neuronal losses in young and aged male Calomys callosus chronically infected with the MORC-1 strain of Trypanosoma cruzi through numerical quantification of neurons from the myenteric plexus of the colon and quantification of nitric-oxide concentration (NO) during the acute and chronic phase of infection. For this purpose, groups of young C. callosus were infected with the MORC-1 strain of T. cruzi. A group of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The intervention also acted on the proliferation of splenocytes, reducing the proliferative capacity of these cells when exposed to polyclonal stimuli. Regarding neuronal count, the treatment resulted in protection of these cells both in the esophagus [ 22 , 23 ] and in the colon [ 21 ] in both phases evaluated (10 days of infection and 450 days of infection). Regarding morphometric analyses of esophageal neurons (diameter, perimeter, area, and volume), treatment with cyclophosphamide did not induce any changes when the treated and infected groups were compared with the untreated infected group [ 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The intervention also acted on the proliferation of splenocytes, reducing the proliferative capacity of these cells when exposed to polyclonal stimuli. Regarding neuronal count, the treatment resulted in protection of these cells both in the esophagus [ 22 , 23 ] and in the colon [ 21 ] in both phases evaluated (10 days of infection and 450 days of infection). Regarding morphometric analyses of esophageal neurons (diameter, perimeter, area, and volume), treatment with cyclophosphamide did not induce any changes when the treated and infected groups were compared with the untreated infected group [ 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, older animals showed lower values in all parameters analyzed when compared to younger ones [ 23 ]. For colon neurons [ 21 ], the treatment did not induce morphometric changes at 10 days of infection. Only at 450 days of infection, it was observed that the use of cyclophosphamide increased the perimeter, area, and volume of neurons when compared to the respective untreated group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a diversity of strains of T. cruzi that have different biological behaviors, mainly related to molecular biology, tissue tropism, and the form of the developed DC [ 15 , 16 ]. While infection in experimental models with strains such as Y [ 5 , 10 ] and MORC-1 [ 17 ] causes intestinal neuronal destruction, strains such as Ninoa, Queretaro [ 18 ], and Brazil [ 19 ], which induce intestinal changes, have not been evaluated for the number of neurons in the intestinal plexuses.…”
Section: Introductionmentioning
confidence: 99%